Indocyanine Green Near-Infrared Fluorescence Imaging-Guided Laparoscopic Heminephrectomy for Left Ureteral Cancer in Patient with Horseshoe Kidney - Takao Natsuyama; Yozo Mitsui; Masato Uetani; Shigeyuki Ohta; Shin-ichi Hisasue (Case Reports in Urology)
Laparoscopic surgery for patients with a horseshoe kidney is challenging because of the location, aberrant vasculature, and difficulty with division of the isthmus with adequate hemostasis. We herein report performance of a laparoscopic heminephrectomy for left ureteral cancer in a patient with a horseshoe kidney under guidance from near-infrared fluorescence (NIRF) imaging using indocyanine green (ICG). A 62-year-old male was referred to our hospital for treatment of left ureteral cancer associated with a horseshoe kidney. We performed a laparoscopic left nephroureterectomy and bladder resection in June 2017. During the operation, the NIRF imaging system was used to evaluate the border of the kidney parenchyma isthmus after ligation of the left kidney vasculature supply. Interestingly, the dominant region of the right kidney showed strong ICG fluorescence as compared to the left kidney region. With the assistance of ICG-based NIRF imaging, isthmus division was performed with monopolar scissors and adequate hemostasis was obtained by electrocautery coagulation. This is the first report of use of an ICG-based NIRF imaging system and this novel approach can help to demarcate the left moiety isthmus from right one with more certainty.